Evaluating System Reliability of Floating Offshore Substations - Morteza, Ahmadivala; Schoefs, Franck; ICASP14; Oumouni, Mestapha; Luxcey, Neil; Dupriez-Robin, Florian (My University, 2023)
Offshore wind is planned to become the first source of energy by 2050 in view to meet the required levels of CO2 emissions in the world. That requires to install turbines in deeper seas. It is shown that only Floating Wind Turbines will permit to deal with this challenge while keeping a reasonable cost of energy production and transport according to the Levelized Cost Of Electricity. In a lot of sites, Floating Offshore SubStation (FOSS) will be needed. This technology is still at a low Technology Readiness Level. This paper aims at analyzing the system reliability of such a structure for which failure rates of structural components such as mooring lines and dynamic power cables are close to the ones of electrotechnical systems. As a consequence, only a system reliability assessment of the FOSS will allow quantifying accurately its availability and the most sensitive components for Operation and Maintenance planning. Usually, structural reliability aims at quantifying probability of failures when electro-technical reliability relies on feedback and observed failure rates. The paper first unified these two concepts in a single formalism and then formalized the system reliability and its availability. This methodology is illustrated on a study case designed in the French LISORE project. The study case is localized in the French coasts of Mediterranean Sea where the effect of several mooring design and substation design on the system reliability are compared.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED